Effect of Sucrose Spray on some Phytochemical Characteristics of Stevia (Stevia rebaudiana Bertoni) under Field Conditions - Vahid Akbarpour; Hossein Aruei; Kambiz Mashayekhi; Majid Azizi Arani; Mohammad Ali Bahmanyar (پژوهشنامه اصلاح گیاهان زراعی)
Extended Abstract Background: Sugars are one of the important components in the human diet, along with fats and proteins, which provide about 60-70% of their energy. Stevia is one of the most important medicinal plants with high antioxidant properties, obvious sugar characteristics, and without calories, which can replace sugars extracted from other sources. One of the features of this sweetener is that it is very useful for diabetics due to its lack of absorption in the digestive system. On the other hand, it is suitable for the diet of obese people due to its non-caloric nature. Sucrose is the transportable form of photosynthetic products, i.e. carbohydrates, in plants. Sucrose foliar spraying is important for the quick supply of compounds needed by plants. Methods: This factorial experiment was carried out based on a randomized complete block design (RCBD) with four replications at Sari Agricultural Sciences and Natural Resources University from 2014 to 2015. Evaluated treatments consisted of different concentrations of a sucrose solution (0, 2.5, 5, and 10%). Thus, the mentioned material was diluted in solvents such as methanol 15%, boric acid (3 ppm), and acetic acid (1 ppm). Treatments were sprayed on plants at 10-day intervals until plants started the flowering stage. Some parameters, such as total chlorophyll, carotenoids, total phenol, total flavonoid, antioxidant activity, steviozide, and ribodiozide contents were measured at the beginning of flowering. Results: The results of the analysis of variance showed that the simple effect of the solvent type and sucrose concentration on all studied traits at the probability level of 0.01 and the interaction effect of the treatments on all traits, except for the amount of ribodiozide, were significant at the probability level of 0.05 and on the amount of steviozide at the probability level of 0.01. The average data comparison results showed that the amount of total chlorophyll in 10% sucrose concentration was significantly higher than the other sucrose concentrations. There was a significant difference between different concentrations of sucrose in terms of carotenoid content so that the highest (10.72 mg/g fresh weight) and the lowest (9.56 mg/g fresh weight) levels were recorded at concentrations of 5% and 0% sucrose, respectively. The amount of carotenoid in the methanol solvent (11.99 mg/g fresh weight) was significantly higher than in the other solvents, namely boric acid, acetic acid, and distilled water (its lowest amount). The amount of flavonoid was significantly different between different concentrations of sucrose and also in different solvents. Five percent sucrose concentration (10.82 mg of quercetin per gram of dry weight) and zero percent sucrose concentration produced the lowest (9.31 mg of quercetin per gram of dry weight) flavonoids. Based on the results of the data, the highest and lowest flavonoid contents were obtained in methanol (11.51 mg quercetin per gram of dry weight), boric acid (10.74 mg quercetin per gram of dry weight), acetic acid (9.42 mg quercetin per gram of dry weight) ), and distilled water (8.32 mg of quercetin per gram of dry weight) solutions, respectively. The amount of total phenol in the 5% sucrose concentration (19.54 mg of gallic acid per gram of dry weight) was significantly higher than in other concentrations. The results of comparing the average data showed a significant difference between different solvents in terms of the amount of total phenol so that the methanol solvent (23.07 mg of gallic acid per gram of dry weight) and the distilled water solvent (13.47 mg of gallic acid per gram of dry weight) contained the highest the lowest total phenol contents, respectively. The results obtained from this research showed a significant difference between different concentrations of sucrose in terms of the amount of antioxidants so that the highest (85.71%) and lowest (62.38%) amounts were found in five and zero percent concentrations, respectively. Based on variance analysis data, there was a significant difference in the amount of antioxidants in different solvents, and the highest and the lowest amounts were observed in methanol (90.59%) and distilled water (69.87%) solvents, respectively. Based on the obtained results, the methanol solvent had the highest (14.01%) and the distilled water solvent produced the lowest (11.27%) amounts of steviozide. Based on the comparison of average data, the lowest (5.77%) and the highest (13.01%) amounts of steviozide were measured at concentrations of 10% and 5% sucrose, respectively. According to the results of comparing the average concentrations of different sucrose levels on the amount of ribodiozide, the concentrations of 0% and 5% sucrose led to the lowest and the highest amounts of ribodiozide, respectively. According to the effect of the solvent, the highest and lowest amounts of ribodiozide belonged to methanol and distilled water solvents, respectively. Based on the mean comparison analysis, the most optimum amount of photosynthetic and phytochemical parameters were related to the concentration of 5% sucrose while the other concentrations were in the next orders. Moreover, the highest and the lowest optimum amounts were recorded in the methanol (15%), boric acid (3 ppm), acetic (1 ppm), and distilled water (control) solvents, respectively. Conclusion: The studied carbon sources had a significant effect on many investigated traits. An increase in the concentration of assimilated carbohydrates as a result of sucrose application at a concentration of 5% with the methanol solvent may increase the availability of respiratory intermediates, which results in the reduction of non-photochemical energy loss. The occurrence of these biochemical phenomena caused by the consumption of intermediate substances ultimately increases the photosynthetic efficiency and improves the accumulation of photosynthetic substances, as well as the synthesis of secondary metabolites. Finally, it can be concluded that the application of sucrose with its appropriate solvent (methanol) could decrease or replace the absolute requirement for carbon source in the environment.